Macroporosity and Grain Density of Rubble Pile Asteroid (162173) Ryugu. Issue 12 (4th December 2020) - Grott, Matthias; Biele, Jens; Michel, Patrick; Sugita, Seiji; Schröder, Stefan; Sakatani, Naoya; Neumann, Wladimir; Kameda, Shingo; Michikami, Tatsuhiro; Honda, Chikatoshi
Abstract: Rubble pile asteroids such as (162173) Ryugu have large bulk porosities, which are believed to result from void spaces in between the constituent boulders (macroporosity) as well as void spaces within the boulders themselves (microporosity). In general, both macroporosity and microporosity are estimated based on comparisons between the asteroid bulk density and both the bulk and grain density of meteorite analogs, and relatively large macroporosities are usually obtained. Here we use semiempirical models for the macroporosity of multicomponent mixtures to determine Ryugu's macroporosity based on the observed size‐frequency distribution (SFD) of boulders on the surface. We find that Ryugu's macroporosity can be significantly smaller than usually assumed, as the observed SFD allows for an efficient packing of boulders, resulting in a macroporosity of 16% ± 3%. Therefore, we confirm that Ryugu's high bulk porosity is a direct consequence of a very large boulder microporosity. Furthermore, using estimates of boulder microporosity of around 50% as derived from in situ measurements, the average grain density in boulders is 2, 848 ± 152 kg m –3, similar to values obtained for CM and the Tagish lake meteorites. Ryugu's bulk porosity corresponding to the above values is 58%. Thus, the macroporosity of rubble pile asteroids may have been systematically overestimated in the past. Plain Language Summary: The carbonaceous asteroid (162173) Ryugu formed from fragments which reaccreted after its parent body was disrupted by a catastrophic collision. Asteroids of this type are also known as rubble piles and the reaccumulation process is thought to be one of the causes for their large bulk porosity. We have applied mixing models to determine the amount of interboulder porosity taking the observed abundance of large and small boulders on the surface into account. We find that the relative abundances of differently sized boulders allow for a very efficient packing, such that interboulder porosity in Ryugu is rather small and only 16% ± 3%. This implies that a large part of Ryugu's total porosity must reside inside the boulders themselves. Using estimates of boulder intrinsic porosity, we furthermore constrain the average density of the boulder's constituent minerals to 2, 848 ± 152 kg m −3, which is consistent with values measured for carbonaceous meteorites as collected on Earth. Thus, interboulder porosity of rubble pile asteroids may have been systematically overestimated in the past. Key Points: Ryugu's large bulk porosity is distributed between intrinsic boulder microporosity and macroporosity due to void spaces in‐between boulders We use the boulder size‐frequency distribution as observed on the surface together with mixing models to estimate Ryugu's macroporosity We find that macroporosity is 16% ± 3%, indicating that Ryugu's large bulk porosity of close to 50% is governed by microporosity